Vulnerability assessment and strengthening of R.C. buildings non-seismically designed - Varum, H. (2012)
The seismic vulnerability associated with existing buildings, constructed until the late 1970’s, in urban areas in most southern European countries, with moderate to high seismic risk, is of extreme importance. In that period, reinforced concrete buildings were designed and constructed without considering earthquake provisions, constituting a significant risk. Recent major earthquakes around the world have evidenced that this type of existing buildings lacking appropriate seismic resisting characteristics are very vulnerable. Their retrofit should be made in order to reduce vulnerability, and consequent risk, to currently accepted levels. Despite the evident advantages of a refined non-linear dynamic structural fibre modelling, it must be admitted that this approach can frequently become elaborated and costly. Simplified non-linear static models considering just one DOF (such the Capacity Spectrum Method) are frequently not able to assess accurately irregular structural systems. These facts sustain the development of less complicated structural models without debasing the essential features of dynamic response. It is demonstrated a recently proposed simplified methodology for nonlinear dynamic analysis of buildings based on the multi-modal spectral seismic response, and an optimisation tool for the strengthening design of existing buildings.